Product life cycle management in engineer-to-order industries. (5th May 2009) - Hicks, Christian; McGovern, Tom
This paper analyses the characteristics of Engineer-To-Order (ETO) companies, their markets, products, internal processes and supply chains. ETO companies design, manufacture and construct plant that is highly customised. The products are complex and supplied in low volume to global markets. Privatisation and deregulation have changed the competitive criteria and the products and services required by customers, which has led to a restructuring of the ETO industry. Customers are increasingly requiring turnkey projects and through-life solutions. Design is a core capability of ETO companies. Design can involve incremental or radical innovation. Project, risk and supply chain management are important competencies. Design change control, stage-gate systems and Capability Maturity Models show particular promise for helping ETO companies manage the product life cycle.